Burden of leishmaniasis in Brazil and federated units, 1990-2016: Findings from Global Burden of Disease Study 2016. - Juliana Maria Trindade Bezerra; Valdelaine Etelvina Miranda de Araújo; David Soeiro Barbosa; Francisco Rogerlândio Martins-Melo; Guilherme Loureiro Werneck; Mariângela Carneiro (PLoS Neglected Tropical Diseases, 2018)
BACKGROUND:The study presents estimates for the burden of visceral leishmaniasis (VL) and cutaneous and mucocutaneous leishmaniasis (CML) in Brazil and its 27 federated units using data from the Global Burden of Disease Study (GBD) 2016. METHODOLOGY:We report the incidence, years of life lost (YLL), years lived with disability (YLD), and disability-adjusted life years (DALY) for leishmaniasis in Brazil from 1990 to 2016. The metrics are presented as age-standardized rates per 100,000 inhabitants with their respective uncertainty intervals (95%UI) and relative percentages of change. PRINCIPAL FINDINGS:The age-standardized incidence rate of leishmaniasis decreased 48.5% from 1990 (71.0, 95%UI 24.3-150.7) to 2016 (36.5, 95%UI 24.7-50.9), whereas the age-standardized DALY increased 83.6% over the studied period from 12.2 (95%UI 7.9-18.8) to 22.4 (95%UI 13.3-36.2). The age-standardized incidence rate and YLL for VL increased by 52.9% and 108% from 1990 to 2016, respectively. Considering CML, the age-standardized incidence rate and YLD decreased by 51% and 31.8% respectively for the same period. For VL, similar profiles for male and female were observed, with YLL and DALY increasing over time; with males presenting slightly higher values. The highest YLL rates were among "under 1-year old" children, which increased 131.2% from 1990 to 2016. Regarding CML, the highest values of YLD and DALY were verified among males, and YLD values showed a similar profile, with rates increasing with age. The VL burden increased in some states in the Northeast and Southeast regions and decreased for CML in some Northern states. CONCLUSION:The increase of VL burden over the study period might be associated with the difficulties in controlling the disease spread. Information regarding the weight of VL and CML, including the death and disability tolls that they cause, highlights the impact of these neglected diseases on public health and the importance of effective prevention and treatment.